A Compendium of Policy Instruments to Enhance Financial Stability and Debt Management in Emerging Market Economies - Mendoza, Ronald U (Archīum Ateneo, 2007)
Drawing on the available theory and empirical evidence, this paper attempts to map out some of the key factors that contribute to international financial instability. It then uses this to develop a possible taxonomy for the array of proposed (and some already existing) policy instruments designed to enhance financial stability and debt management in emerging market economies. The purpose of this taxonomy is to relate each instrument to the particular aspect(s) of the broader policy challenge, thus clarifying differences and/or similarities across these instruments and proposals. The analysis herein suggests that instruments that could help increase the efficiency of risk management strategies (such as growth- or GDP-indexed bonds) and enhance the effectiveness of debt management, growth and development policies (such as a stability and social investment facility or SIF) need to be considered further.